Antibacterial properties of silver nanoparticle (AgNPs) on stainless steel 316L - Aminatun; Furqon, Ilham Alif; Hikmawati, Dyah; Che Abdullah, Che Azurahanim (Tehran University of Medical Sciences, 2021)
Objective(s) : The probability of contracting an infection when implanting an Stainless Steel 316L (SS316L) implant has been increasing. Infection due to implant placement is called osteomyelitis which is bone inflammation caused by biofilms formed by pyogenic bacteria. Biofilms can be prevented by giving antibacterial agents. This study aims to examine the potential of silver nanoparticles (AgNPs) as an antibacterial agent in SS316L implants. Methods : AgNPs are made through a chemical synthesis process using the Gallic acid reduction method. AgNPs solution with 5 variations of precursor concentration, namely 0.1 mM, 1 mM, 10 mM, 100 mM each added with gelatin was sprayed on SS316L by the airbrush spray coating method with a distance between nozzle and substrate of 20 cm at a pressure of 40 psi. Result : AgNPs solutions produced from various concentrations of AgNO3 precursors have a range of λmax = 401.5 nm- 424.5 nm and a particle size distribution of 0.97 - 4.88 nm. The AgNPs layer on SS316L was characterized by its crystalline phase, crystal size, and anti-bacterial activity. It has a cubic structure with a phase fraction of 6.5-19%. Based on the antibacterial activity test, all AgNPs layer samples had inhibitory zone diameters in the range of 12-16 mm. AgNPs (10mM) + Gelatin layer showed the best antibacterial ability with an inhibitory zone diameter of 16.63 mm. Conclusion : The variation in the concentration of the 10 mM AgNPs precursor-Gelatin can be developed into a coating on the surface of the SS316L implant material.